CLINICAL CHARACTERISTICS OF EYES WITH DIFFERENT GRADES OF MYOPIC TRACTION MACULOPATHY: Based on the New Classification System. Issue 7 (July 2021) - Li, Jun; Liu, Bingqian; Li, Yonghao; Zhao, Xiujuan; Chen, Shida; Huang, Xia; Lian, Ping; Li, Tao; Jin, Chenjin; Liang, Xiaoling; Lu, Lin
Abstract : Purpose: To analyze clinical characteristics in eyes with myopic traction maculopathy (MTM). Methods: Nine hundred and ninety-one patients (1, 334 eyes) with MTM, who visited Zhongshan Ophthalmic Center from January 2014 to December 2019, were involved. Myopic traction maculopathy was classified into six grades according to the new classification system: no macular schisis (T0), inner or outer foveoschisis (FS) (T1); inner and outer FS (T2), foveal detachment (T3), full-thickness macular hole (T4), and macular hole retinal detachment (T5). Results: Seven hundred and seventy-eight (58.32%) eyes were in T0, 157 (11.77%) in T1, 177 (13.27%) in T2, 129 (9.67%) in T3, 45 (3.37%) in T4, and 48 (3.67%) in T5. With the severity of MTM, age increased and the best-corrected visual acuity became worse ( P < 0.001). However, no significant differences were found on spherical equivalent refraction or axial length among different grades of MTM ( P > 0.05). Moreover, significant differences on best-corrected visual acuity, spherical equivalent refraction, axial length, and staphyloma rate existed between eyes with inner FS and eyes with outer FS ( P < 0.01), but not between eyes with outer FS and eyes with both inner FS and outer FS ( P > 0.05). Besides, significant differences were found on spherical equivalent refraction, axial length, and staphyloma rate between full-thickness macular hole with and without macular schisis ( P < 0.001). Conclusion: Spherical equivalent refraction and axial length were not correlated with the severity of MTM in this cohort. It might be preferable to categorize eyes with outer FS and eyes with both inner FS and outer FS as a same grade. Potential difference in the pathogenesis between full-thickness macular hole with and without macular schisis might exist. Abstract : This is a study to investigate the clinical characteristics in eyes with different grades of myopic traction maculopathy according to the new classification system.